Scalable and multiplexed recorders of gene regulation dynamics across weeks - Lirong Zheng; Dongqing Shi; Yixiao Yan; Bingxin Zhou; Jormay Lim; Yongjie Hou; Bobae An; Jason K. Adhinarta; Michael Lin; BumJin Ko; William C. Joesten; Mehul Gautam; et al. (Nature, 2026)
Abstract Gene expression is dynamically controlled by gene regulatory networks comprising multiple regulatory components to mediate cellular functions 1 . An ideal tool for analysing these processes would track multi-component dynamics with both spatiotemporal resolution and scalability within the same cells, a capability not yet achieved. Here we present CytoTape, a genetically encoded, physiologically compatible, modular protein tape recorder for multiplexed and spatiotemporally scalable recording of gene regulation dynamics continuously for up to 3 weeks, with single-cell, up to minutes-scale resolution. CytoTape uses a flexible, thread-like, elongating intracellular protein self-assembly engineered via computationally assisted rational design, built on our earlier XRI technology 2 . We demonstrate its utility across multiple mammalian cell types, achieving simultaneous recording of five transcription factor activities and gene transcriptional activities. CytoTape reveals that divergent transcriptional trajectories correlate with transcriptional history and signal integration, and that distinct immediate early genes (IEGs) exhibit complex temporal correlations within single cells. We further extended CytoTape into CytoTape-vivo for scalable, spatiotemporally resolved single-cell recording in the living brain, enabling simultaneous weeks-long recording of doxycycline-dependent and IEG promoter-dependent gene expression histories across up to 14,123 neurons spanning multiple brain regions per mouse. Together, the CytoTape toolkit establishes a versatile platform for scalable and multiplexed analysis of cell physiological processes in vitro and in vivo.